Localization of FGF21 Protein and Lipid Metabolism-Related Genes in Camels - Yuan Gao; Shuqin Zhao; Wangdong Zhang; Huaping Tang; Meilin Yan; Fang Yong; Xu Bai; Xiaochun Wu; Yong Zhang; Quanwei Zhang (Life, 2023)
With the ability to survive under drought and chronic hunger, camels display a unique regulation characteristic of lipid metabolism. Fibroblast growth factor (FGF) 21 is a peptide hormone that regulates metabolic pathways, especially lipid metabolism, which was considered as a promising therapeutic target for metabolic diseases. To understand the FGF21 expression pattern and its potential relationship with lipid metabolism in camels, this study investigated the distribution and expression of FGF21, receptor FGFR1, and two lipid metabolism markers, leptin and hormone-sensitive lipase (HSL), using an immunohistochemistry (IHC) assay. The results showed that FGF21 was widely expressed in camel central nerve tissue and peripheral organs but absent in lung and gametogenic tissue, including the testis, epididymis, and ovary. In striated muscle, FGF21 is only present at the fiber junction. FGFR1 is expressed in almost all tissues and cells, indicating that all tissues are responsive to FGF21 and other FGF-mediated signals. Leptin and HSL are mainly located in metabolic and energy-consuming organs. In the CNS, leptin and HSL showed a similar expression pattern with FGFR1. In addition, leptin expression is extremely high in the bronchial epithelium, which may be due to its role in the immune responses of respiratory mucosa, in addition to fat stores and energy balance. This study found that FGF21 showed active expression in the nervous system of camels, which may be related to the adaptability of camels to arid environments and the specific regulation of lipid metabolism. This study showed a special FGF21-mediated fat conversion pattern in camels and provides a reference for developing a potential therapeutic method for fat metabolism disease.